Narrativas sobre proyecto de vida, relaciones parentales y sociales de mujeres bisexuales (2023)
The present work of degree was carried out in order to find out if the life project in bisexual women changes according to the social and family environments. An in-depth interview was implemented, which allowed a narrative design with qualitative methodology. In this interview it was found that bisexual women from the concept of systemic theory allow themselves to reflect on their sexuality, which addresses different and broad ideas regarding the relationship with family and social dynamics. This also allowed to focus on the life project, which is usually dynamic, allowing to change or modify personal aspects in the course of life, determining also the family support, which is sometimes perceived as overprotection, giving an emotional impact on the acceptance or not of themselves, which use coping strategies such as avoidance through escape or flight.